Znaki obowiązujące na krytych pływalniach jako system wspomagający bezpieczeństwo i higienę wodnej aktywności rekreacyjno-sportowej = Signs binding at indoor pools as a system supporting the safety and hygiene of water recreational and sport activity - Wioletta Łubkowska; Mirosława Szark-Eckardt; Hanna Żukowska (Kazimierz Wielki University, 2015)
Łubkowska Wioletta, Szark-Eckardt Mirosława, Żukowska Hanna. Znaki obowiązujące na krytych pływalniach jako system wspomagający bezpieczeństwo i higienę wodnej aktywności rekreacyjno-sportowej = Signs binding at indoor pools as a system supporting the safety and hygiene of water recreational and sport activity. Journal of Education, Health and Sport. 2015;5(11):551-564. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35697 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A551-564 http://pbn.nauka.gov.pl/works/684761 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Original Text published © The Author (s) 2015. Łubkowska Wioletta, Szark-Eckardt Mirosława, Żukowska Hanna. Znaki obowiązujące na krytych pływalniach jako system wspomagający bezpieczeństwo i higienę wodnej aktywności rekreacyjno-sportowej. Quality in Sport. 2015;1(3):7-19. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%283%29%202015%2C%20s.%207-19   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   Wioletta Łubkowska Wydział Kultury Fizycznej i Promocji Zdrowia, Uniwersytet Szczeciński Mirosława Szark-Eckardt, Hanna Żukowska Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Znaki obowiązujące na krytych pływalniach jako system wspomagający bezpieczeństwo i higienę wodnej aktywności rekreacyjno-sportowej Signs binding at indoor pools as a system supporting the safety and hygiene of water recreational and sport activity       Streszczenie                 Celem badań było określenie stopnia i charakteru zagrożeń występujących w strefie oznakowania pływalni krytych odnoszących się do wymaganych zasad bezpieczeństwa. Badania przeprowadzono na 29 obiektach, zlokalizowanych na terenie dziesięciu województw. Posłużono się metodą jakościowych badań terenowych oraz metodą badań niereaktywnych. Stwierdzono, iż w ponad połowie badanych pływalni krytych (51,7%) znak zakazu A-8 "skakanie do wody zabronione" miał formę graficzną niezgodną z obowiązującymi przepisami. Znaki informacyjne: C-2 - "niebezpieczna głębokość wody" i C-3 - "nagły uskok" wystąpiły tylko w 27,6% badanych obiektów. W zakresie znaków pozaprawnych - komunikatorów stwierdzono, że nie istnieje ujednolicony sposób przekazywania informacji. Używana symbolika jest bardzo różnorodna, co powoduje chaos w postaci różnych oznakowań. W celu zwiększenia bezpieczeństwa osób korzystających z pływalni krytych należałoby podjąć działania zmierzające do opracowania i wprowadzenia ujednoliconych wzorów oznaczeń, co stanowi konieczny warunek pełnego uczestnictwa we współczesnej kulturze fizycznej.   Słowa kluczowe: pływalnia kryta, parki wodne, bezpieczeństwo, higiena, znaki, piktogramy, ratownictwo wodne, WOPR.       Abstract                 The aim of the research was to determine the level and nature of risks occurring in the sign zone of indoor pools relating to required safety rules. The research was conducted at 29 facilities located in ten provinces. The method of qualitative field research was applied. It was found that at more than half of the examined indoor pools (51.7%) the A-8 prohibitory sign "jumping into water is prohibited" had the graphic form that was inconsistent with the binding provisions. The information signs: C-2 - "dangerous depth of water" and C-3 - "sudden drop" occurred only at 27.6% of examined facilities. Within the scope of non-legal signs - communicators it was found that there is no uniform manner of providing information. The symbols used is very diverse which causes chaos in the form of various markings. In order to improve the safety of persons using the indoor pools, activities aiming at developing and introducing uniform models of markings should be undertaken, which constitutes a necessary condition of full participation in modern physical culture.   Key words: indoor pool, water parks, safety, hygiene, signs, pictograms, water rescue, WOPR [Volunteer Water Rescue Service].